DESIGN OF 26-STORY EARTHQUAKE RESISTANT REINFORCED CONCRETE STRUCTURE IN JAKARTA - Miranti Chastra, Dwina
This final project contains the process of designing reinforced concrete office structures located in Jakarta. Office buildings have a total of 26 floors with a total height of 110.64 m. In this building there are functions of offices and lobby lifts on one floor for floors 1 to 25, one floor for mechanics on the 26th floor, and the upper part functions as a flat roof. The seismic structural system used is a dual system, consisting of Special Moment Frames (SMF) and Special Structural Wall (SSW). The building structure is modeled using ETABS and designed based on SNI 1726- 2012 for earthquake resistant building analysis, SNI 2847-2013 for reinforced concrete building designs, and SNI 1727-2013 for gravity loading. Earthquake resistant building analysis consists of checking structural irregularities, P-Delta effect, story drift, dual system, redundancy factors, and collector elements. Structural element detailing is done manually for beams, columns, joints, shear walls, coupling beams, and diaphragms based on internal forces obtained from ETABS. Detailed plate elements will be assisted by SAFE software.